Epidermal growth factor (EGF) in the gastroprotective and ulcer healing actions of colloidal bismuth subcitrate (De-Nol) in rats. Issue 7 (July 1988) - Konturek, S J; Dembinski, A; Warzecha, Z; Bielanski, W; Brzozowski, T; Drozdowicz, D
Abstract : Colloidal bismuth subcitrate (CBS; De-Nol) exhibits gastroprotective properties in experimental animals and enhances the healing of chronic gastroduodenal ulcers, but the mechanisms of these actions have not been entirely elucidated. The present study was designed to determine whether epidermal growth factor (EGF), which also has gastroprotective and ulcer healing properties, contributes to the action of De-Nol on the stomach in rats. It was found that De-Nol protects the gastric mucosa against ethanol damage and that this is accompanied by increased mucosal generation of prostaglandins (PG). Removal of the endogenous source of EGF (sialoadenectomy) did not significantly decrease the protective and PG stimulating effects of De-Nol. Pretreatment with exogenous EGF partially protected the stomach against ethanol injury, but did not influence the protective action of De-Nol in sialoadenectomised animals. De-Nol, like EGF given orally, enhanced the healing of chronic gastric and duodenal ulcers induced by serosal acetic acid. De-Nol was found to bind EGF in a pH-dependent manner and to accumulate it in ulcer area. Thus the peptide is available locally in high concentrations to accelerate the re-epithelialisation and tissue repair of the ulcerated mucosa. These ulcer healing effects of De-Nol were reduced by sialoadenectomy and restored in part by oral administration of EGF. We conclude that salivary glands in rats are not essential for the gastroprotection induced by De-Nol, but seem to play an important role in the ulcer healing action of this drug possibly via an EGF mediated mechanism.